Analisis Metode Dakwah Ustaz Ariadi Banarto Di Sidikalang Kabupaten Dairi - Benny Munardi; Latiful Ilham Ujung (Program Studi Komunikasi dan Penyiaran Islam, 2022)
The purposes of the studies were to determine the da'wah method of Ustadz Ariadi Banarto in Sidikalang, Dairi Regency. This type of research is qualitative research with a descriptive approach. Sources of data through interviews, observation, and documentation. Data analysis techniques are recording all the data collected, sorting the data, and conducting an in-depth study of the data. The data validity technique is the persistence of observation and triangulation. The results showed that Ustaz Ariadi Banarto used the method of wisdom, good advice, and discussion in preaching in Sidikalang, Dairi Regency. The obstacles obtained are in terms of language, the busyness of the community with work, the existence of community groups who reject their preaching, and the public's lack of understanding of the material presented.